MACAM DAN DOSIS PUPUK ORGANIK TERHADAP HASIL DAN KADAR ANTOSIANIN KELOPAK BUNGA ROSELA (Hibiscus sabdariffa) - Sumarno Sumarno (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2010)
Title: Kinds and doses of organic fertilizers on the yield and anthocyanin content of Roselle calyx (Hibiscus sabdariffa). A Roselle petal has fresh taste and attractive red color. In addition to containing high vitamin C which also contains the pigment anthocyanin, can be processed into several products that have high economic value. Drug efficacy from Rosella interest include lowering high blood pressure, lower levels of fat and cholesterol, blood circulation, stop cough and facilitate defecation. Increasing crop productivity can be done by providing additional nutrients through the selection of appropriate types of fertilizer, effective and efficient. Vermicompost and fermented organic fertilizer, besides containing the elements necessary macro plants also contains elements such as micro-and growth hormone auxin, cytokinin and gibberellins. The research aims to find out kind of organic fertilizer and the correct dosage to improve results rosella flower petals with high anthocyanin content. Research was done in Jumantono Village, Karanganyar. Is a field trial, RAKL nested with treatment: Various Organic Fertilizers: Bokhasi, Casting, and compost. Dose of fertilizer each: 3; 6; 9 tons / ha. Conclusion, vermi fertilizer to increase growth and yield of Roselle calyx higher compared with fermented manure and compost, vermi fertilizer 9 t / ha is able to provide the highest dry weight of petals compared with the dose and under control. While fertilizer fermented 6 t / ha have been able to increase yields and high dose up to 9 t / ha increase in the result does not mean; dose of compost and fermented which gives a high anthocyanin content is 9 t / ha, while the dose of fertilizer Vermicompost 6 t / ha have been able to provide a high anthocyanin content and increased the dose to 9 t / ha increment is not significant. Keywords: anthocyanin, Hibiscus sabdariffa, organic fertilizer, Vermicompost